Terms of trade movements and the global economic crisis: Implications for the Asia-Pacific region - Bloch, Harry; Sapsford, D. (The Australian National University, 2009)
Dramatic changes in the relative prices of goods in international trade have accompanied, and indeed preceded, the global crisis. These changes are reflected in the terms of trade ofindividual countries and in the relative prices of goods within those countries. Asia-Pacific countries are particularly affected by the changes in relative prices as they have been at the core of the increasing globalisation of production and distribution systems. An analysis of the causes and effects of the relative price changes is developed based on applying the analysisof business cycles developed by Joseph Schumpeter. Schumpeter's analysis emphasises innovation and structural change, particularly creative destruction, which impart uneven development on the economy and can foster financial crises. By applying Schumpeter's analysis the current crisis is put in the context of long-wave development of the capitalist system, which leads to predictions about the likely path of price and output changes over the medium term of the next decade or two.